2014
DOI: 10.1002/bjs.9635
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of live surgical demonstrations and their effectiveness on training

Abstract: Little evidence exists on the safety and educational value of live surgery, with few studies of high quality conducted. Guidance on live procedures is scarce, with only three major surgical specialties offering any advice. More needs to be done to establish and promote evidence for the value of live surgery demonstrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
(73 reference statements)
0
20
0
1
Order By: Relevance
“…Overall, data comparing the outcomes of live case presentations with cases undertaken in normal settings are scarce, and no pediatric report is available as of today. Brunckhorst et al [10] reviewed the literature from 1980 until 2014 on live surgery outcomes, identifying eight studies in differ- Table 2. Recommendations to ensure patient safety during live surgery events…”
Section: Discussionmentioning
confidence: 99%
“…Overall, data comparing the outcomes of live case presentations with cases undertaken in normal settings are scarce, and no pediatric report is available as of today. Brunckhorst et al [10] reviewed the literature from 1980 until 2014 on live surgery outcomes, identifying eight studies in differ- Table 2. Recommendations to ensure patient safety during live surgery events…”
Section: Discussionmentioning
confidence: 99%
“…The attendance of live surgery events is an established means of learning anatomy as well as novel surgical techniques in nearly all surgical disciplines [20]. However, the demonstration of surgical procedures in real patients at live surgery events is subject to critical discussion from an ethical point of view [21,33]. Several studies have shown a potentially negative impact on the outcome of patients who have undergone live surgery, which is opposed to the no-harm principle of medicine [24][25][26]34].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the attendees are able to communicate with the surgeons during video transmission [18]. A large number of surgeons are introduced to new surgical techniques and the relevant clinical anatomy is demonstrated on a single patient [19,21]. Furthermore, live surgery events offer the opportunity to learn from experts as a role model in real life, as well as handle surgical complications and manage difficult cases appropriately [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, observational studies, comparing the outcomes of LSD with routine practice, give less cause for concern [ 6 , 13 , 14 ]. Brunckhorst et al reviewed the literature from 1980 until 2014 on LSD outcomes, identifying eight studies in different medical fields.…”
Section: Discussionmentioning
confidence: 99%
“…Brunckhorst et al reviewed the literature from 1980 until 2014 on LSD outcomes, identifying eight studies in different medical fields. In three of these studies, the success rates of LSD were lower than of routine practice, yet there were no statistically significant differences in complication rates [ 13 ]. More recently, three studies evaluated the outcomes of live endourological procedures and live robot-assisted radical prostatectomies.…”
Section: Discussionmentioning
confidence: 99%